Organizational Capacity Development and Innovation: The Case of Tunisian High-Tech Companies - HAMDI, Rahma (LPPM of NAROTAMA UNIVERSITY, 2025)
This article examines the impact of organizational capacity development on the innovation potential of companies. Based on a survey conducted with 32 high-tech sector companies, the study highlights that enhancing skills, knowledge, and resources within organizations promotes their ability to innovate. Statistical analysis, carried out using SPSS version 25, confirms a positive correlation between these organizational capacities and company performance. This underscores their crucial role in ensuring survival and growth in an ever-evolving economic environment.Keywords: Innovation, organizational capacity, innovation potential.